Comparative Analysis of Green Bond Regimes in Nigeria and China - Oche, Alex (Journal of Sustainable Development Law and Policy, 2025)
Climate change has taken the centre stage in the debate of most governments around the world. At regional and international levels, efforts are being made to manage the problems emanating as a result of climate change. Response to the climate change can be summarized under two headings, namely, adaptation and mitigation measures. These measures do not come by cheaply, however. They are capital intensive; hence private sector funds will be needed to fund these adaptation and mitigation projects as public sector funding has remained insufficient. One way to mobilize private sector funds to tackle climate change is by using green bonds. But for green bonds to achieve its potentials as a sustainable investment tool, there must be a solid regulatory framework for the green bond market. Towards that end, this article analyses soft law instruments as well as national green bond regulations of Nigeria and China. It has been discovered that the Climate Bonds Standard and the Green Bond Principles form the basis of most jurisdictions of green bond regulations. nevertheless, due to regulatory arbitrage, there is no consensus green standard, and this poses a governance challenge to the green bond market. The article concludes that much of the responsibilities in setting green standards and enforcement of green standards rest on the domestic green bond regulations, and this can only be achieved with water-tight regulations for green bonds at domestic levels.